Rādhā-Kṛṣṇa’s Vedāntic debut: chronology and rationalisation in the Nimbārka Sampradāya - Ramnarace, Vijay Nischol (The University of Edinburgh, 2015)
In this thesis I provide an additional perspective on the development of Rādhā- Kṛṣṇa who are regarded as the central divinity in many religious traditions in South Asia, by examining the primary sources of the Nimbārka Sampradāya. This school of the Hindu religious tradition of Vaiṣṇavism is unique in its identification of the ontological category of Brahman (the supreme being) solely with Rādhā-Kṛṣṇa, where both are conjointly understood to be the eternal deity, not an avatāra (incarnation) or vyūha (emanation). Previous scholarship on the early phases of this sampradāya has focussed on issues of philosophy and doctrine, with a few attempts beset by demonstrably deficient reasoning at positing a chronology. Although the later tradition has been documented in detail, owing to the absence of a settled chronology, mechanisms of Nimbārkī inter-sectarian relations at this stage of development in early modern Vraja (Braj) have not been satisfactorily established. In Part One, I provide a survey of the current theories on the development of Kṛṣṇa (who has received wide scholarly treatment) and Rādhā, re-evaluating Sanskrit and Prakrit textual and epigraphic sources with focus on the divinity of these two figures, positing that although there exist allusions to the godhood of Kṛṣṇa antecedent to the common era, the same cannot be said of Rādhā. Part Two discusses the sources available for Nimbārka and with a view to bringing to light any noteworthy findings, on the basis of comparative studies of the Brahmasūtra commentarial tradition I provide a new chronology for Nimbārka and his immediate followers. Following on from this, I discuss Nimbārka’s works in which is presented his innovation: the deification of Rādhā-Kṛṣṇa. I then examine the rationalisation of this doctrine by Puruṣottama (third successor to Nimbārka), whose exegetical efforts diminish the impact of this teaching in the wider Vaiṣṇava context. In Part Three, I turn to the legacy of Nimbārka and in an important revelation for Vaiṣṇava studies, I show that whilst the early tradition reserved the theological identity of Brahman for the most eligible initiates, in 15th century Vraja a renaissance of Rādhā-Kṛṣṇa devotion was instigated by Keśava Kāśmīrin, Śrībhaṭṭa and Harivyāsa Deva who influenced the contemporary and later sects which, in the modern period, have transported the phenomenon of Rādhā-Kṛṣṇa devotion across the globe.
Keywords: Sanskrit; Vedānta; pre-Śaṅkara; Nimbārka; bhakti